Outcomes of Alvimopan Use in Laparoscopic Intra-abdominal Surgery: A Retrospective Review - Aamir A. Kokan (University of Minnesota Libraries Publishing, 2021)
Background: Postoperative ileus is a transient cessation of bowel motility, occurring after bowel resection, characterized by abdominal distension and pain, nausea, vomiting, and an accumulation of gas/fluids in the bowel. It is associated with a greater incidence of postoperative morbidity and increased length of stay or readmission. Alvimopan, a novel peripheral mu receptor antagonist, is indicated for preventing postoperative ileus in patients undergoing intra-abdominal surgery or bowel resection. The objective of this study was to assess the impact of alvimopan use in laparoscopic abdominal surgeries.